Pengembangan Desa Wisata Berkelanjutan: Studi Kasus di Desa Paccekke, Kabupaten Barru, Indonesia - Ilham Junaid; Wa Ode Dewi; Aristisia Said; Hamsu Hanafi (P4W LPPM IPB, 2022)
This study analyses the actual condition of a tourism village from a sustainable tourism perspective. There is limited study on the implementation of sustainable tourism in tourism villages. This study aims to 1) identify the supporting and inhibiting factors in implementing sustainable tourism; 2) analyse the steps or efforts in achieving sustainable tourism villages. Qualitative research has guided the researchers in collecting data in Paccekke Village, Barru Regency, in 2021. The results reveal supporting and inhibiting factors for implementing sustainable tourism villages. The supporting factors are the natural and cultural potential of the village; sustainable natural conditional; positive attitude of the community towards tourism and the culture of collaborative work (gotong royong); the existence of cultural events; and commitment of local stakeholders. The inhibiting factors are limited facilities and infrastructure, weak planning in the tourism sector, extreme accessibility; weak internet network; and the low awareness and ability of the community in managing tourism potential. This study recommends the importance of utilising the existence of tourist villages in the Barru Regency as a whole in order to improve the quality of tourist visits. Utilising social media as a promotional tool, anticipating the impact of massive visits on environmental quality, and collaborating with various stakeholders for community involvement are strategies to implement sustainable tourism villages. This study provides an overview of the factual conditions of a village, not only from a positive perspective but also obstacles that require solutions or strategies for a sustainable tourism village.